Genomic and Phenotypic Characterization of CHO 4BGD Cells with Quad Knockout and Overexpression of Two Housekeeping Genes That Allow for Metabolic Selection and Extended Fed-Batch Culturing - Nadezhda Alexandrovna Orlova; Maria Valerievna Sinegubova; Denis Eduardovich Kolesov; Yulia Alexandrovna Khodak; Victor Vyacheslavovich Tatarskiy; Ivan Ivanovich Vorobiev (Cells)
Re-engineering of CHO cells using genome editing and the overexpression of multiple helper genes is the central track for obtaining better cell lines for the production of biopharmaceuticals. Using two subsequent rounds of genome editing of the CHO S cells, we have developed the cell line CHO 4BGD with four knockouts of two pro-apoptotic genes bak1 and bax, and two common selection markers genes—glul (GS) and dhfr, and additional copies of genes bcl-2 and beclin-1 used for enhancement of macroautophagy. The NGS sequencing of 4BGD cells revealed that all eight targeted alleles were successfully disrupted. Two edited loci out of eight contained large inserts of non-relevant DNA. Further data analysis shows that cells have no off-target DNA editing events, and all known CHO genes are preserved. The cells obtained are completely resistant to the induction of apoptosis, and they are suitable for the generation of stably transfected cell lines with the dhfr selection marker. They also properly undergo the target gene amplification. The 4BGD-derived clonal cell line that secretes the monoclonal antibody retains the ability for prolonged fed-batch culturing. The method of obtaining multiply edited CHO cells using the multiplex CRISPR/Cas9 editing and simultaneous stable transfection of plasmids, coding for the housekeeping genes, is suitable for the rapid generation of massively edited CHO cells.